Structure and function of the ATP-dependent Clp chaperone/protease machines - Maurizi, Michael R. (Henry Stewart Talks, 2007)
The Clp/Hsp100 family, Structure of Clp complexes, Unfolding and degradation activities of Clps, Substrate recognition and the role of adaptors, ATP utilization, unfolding and translocation, Dynamics of Clp complexes, Protein quality control and the in vivo functions of Clp chaperone/proteases